Accessibility and Engagement - Sarah Crary; Andrea Huseth-Zosel; Erika Beseler Thompson (Flexible Learning Association of New Zealand, 2022)
To reach more students, many colleges are using technology to teach courses via a blended learning model, which allows students to attend class face to face or through a video network. The blended-synchronous format (a blended learning model) is defined as the synchronous instruction of face-to-face and remotely located students. Although it provides flexibility for students in terms of location, the blended-synchronous model also has challenges, including accessibility. This study aimed to understand the expectations and experiences of graduate students who attend blended-synchronous courses. The authors surveyed students in a midwestern, mid-sized research university, who were enrolled in programmes that use the blended-synchronous model. The survey focused on their experiences with, and expectations for, their typical mode of attendance. An analysis of quantitative data using descriptive statistics and independent samples t-tests determined whether there were significant differences between students who attended in person or via a video network (VN) regarding their ideal expectations and actual experiences with classroom engagement. Authors coded open-ended responses to capture and interpret key themes. Results indicated students did not experience significant differences in their ideal or actual classroom engagement regardless of the mode of attendance, although there were significant differences in actual experiences of accessibility-VN students are less able to hear and see the instructor and classmates. Additionally, a sense of "us versus them" emerged between the two groups, with VN students struggling to participate actively. Systems need to be developed to increase participation and social interaction in blended-synchronous courses.